A New Labeling Method of 99mTc-PSMA-HBED-CC - Phromphao, Benchamat; Shiratori, Shuichi (World Journal of Nuclear Medicine, 2025)
68Ga-PSMA-HBED-CC (68Ga-PSMA-11) was approved by the U.S. Food and Drug Administration as the first prostate-specific membrane antigen (PSMA)-targeted positron emission tomography (PET) imaging drug for patients with prostate cancer. However, the utility of 68Ga-PSMA-HBED-CC may be limited due to PET/CT or PET/MR accessibility and 68GaCl3 availability produced from 68Ge/68Ga generator or cyclotron. Thus, in-house preparation of 99mTc-PSMA-HBED-CC was developed as an alternative to 68Ga-PSMA-HBED-CC to be ubiquitous and affordable in the worldwide population.A solution of 99mTc-pertechnetate was added to PSMA-HBED-CC and 4% SnCl2·2H2O in a 10-mL sterile vial. The mixture was heated at 100°C for 15 minutes and then allowed to cool to room temperature. Labeling conditions were optimized to maximize the radiochemical yield of 99mTc-PSMA-HBED-CC. The chelation completeness was monitored using instant thin layer chromatography, and the stability of 99mTc-PSMA-HBED-CC was subsequently evaluated.The radiolabeling of 99mTc-PSMA-HBED-CC was successful using the appropriate amount of 10 µg PSMA-HBED-CC 3 µg SnCl2·2H2O and 99mTc-pertechnetate 370 MBq at 100°C for 15 minutes, yielded the best result in high radiochemical yield (71.49 ± 2.42%), radiochemical purity (98.29 ± 2.65%), and specific activity of 37.84 ± 1.47 GBq/µmol. 99mTc-PSMA-HBED-CC is stable with radiochemical purity of more than 95% within 4 hours at room temperature.A new labeling method of 99mTc-PSMA-HBED-CC was developed. Quality control parameters of 99mTc-PSMA-HBED-CC met the criteria in accordance with the European Pharmacopoeia.
Keywords: prostate cancer; PSMA-HBED-CC; PSMA-11; technetium-99m; 99mTc-PSMA-HBED-CC